Aplicación de la Convención de Nueva York por las cortes Lationamericanas - Cantuarias Salaverry, Fernando (2017)
Through this paper, the authors comment on the application of the Convention on the Recognition and Enforcement of Foreign Arbitral Awards, approved in New York on June 10, 1958, through the review of the most relevant case-law of the main jurisdictions in arbitration in Latin America. The following article provides a review of the different ground for refusal of recognition that a party can use to oppose the recognition of an award, revealing the criteria used by the courts to enforce or deny recognition of a foreign award.